Variation in Actionable Pharmacogenetic Markers in Natives and Mestizos From Mexico - Gonzalez-Covarrubias, Vanessa; Morales-Franco, Marlet; Cruz-Correa, Omar F.; Martínez-Hernández, Angélica; García-Ortíz, Humberto; Barajas-Olmos, Francisco; Genis-Mendoza, Alma Delia; Martínez-Magaña, José Jaime; Nicolini, Humberto; Orozco, Lorena; Soberón, Xavier (Frontiers in Pharmacology, 2019)
The identification and characterization of pharmacogenetic variants in Latin American populations is still an ongoing endeavor. Here, we investigated SNVs on genes listed by the Pharmacogenomics Knowledge Base in 1284 Mestizos and 94 Natives from Mexico. Five institutional cohorts with NGS data were retrieved from different research projects at INMEGEN, sequencing files were filtered for 55 pharmacogenes present in all cohorts to identify novel and known variation. Bioinformatic tools VEP, PROVEAN, and FATHMM were used to assess, in-silico, the functional impact of this variation. Next, we focused on 17 genes with actionable variants that have been clinically implemented. Allele frequencies were compared with major continental groups and differences discussed in the scope of a pharmacogenomic impact. We observed a wide genetic variability for known and novel SNVs, the largest variation was on UGT1A>ACE>COMT>ABCB1 and the lowest on APOE and NAT2. Although with allele frequencies around 1%, novel variation was observed in 16 of 17 PGKB genes. In Natives we identified 59 variants and 58 in Mestizos. Several genes did not show novel variation, in Natives: CYP2B6, CYP2D6, and CYP3A4 or in Mestizos: APOE, UGT1A1, and VKORC1. Similarities in allele frequency, comparing major continental groups for VIP pharmacogenes, hint towards a comparable PGx for drugs metabolized by UGT1A1, DPYD, ABCB1, CBR3, CYP2B6, COMT, and TPMT; in contrast to variants on CYP3A5 and CYP2B6 for which significant MAF differences were identified. Our observations offer some discernment into the extent of pharmacogenetic variation registered up-to-date in Mexicans and contribute to quantitatively dissect actionable pharmacogenetic variants in Natives and Mestizos.